Ecologies of Collective Parent Engagement in Urban Education. (October 2019) - Alameda-Lawson, Tania; Lawson, Michael A.
For the past several decades, the construct of parent involvement (PI) has framed much of the literature on school–family–community partnerships. In this study, the authors used a qualitative form of meta-analysis called thematic synthesis to explore a programmatic alternative to conventional PI known as collective parent engagement (CPE). The CPE approach examined in this study was implemented in three low-income, urban school communities. The primary goal was to help low-income parents develop programs and services that could support the strengths, needs, and challenges of children and families at school and in the community. The findings indicated that, when implemented as an isolated or "stand-alone" service strategy, CPE generally does not influence school outcomes. But when tied to a broader system of reform efforts, CPE can help transform the social-institutional landscape of low-income, urban school communities.